Using eDNA to determine the source of organic carbon in seagrass meadows. (30th March 2017) - Reef, Ruth; Atwood, Trisha B.; Samper‐Villarreal, Jimena; Adame, Maria Fernanda; Sampayo, Eugenia M.; Lovelock, Catherine E.
Abstract: Seagrasses sequester globally significant amounts of carbon (C), which is stored mainly in the sediment. Both C fixation by the seagrass (autochthonous) and the trapping of organic matter that is derived from outside the ecosystem (allochthonous) contribute to seagrass sediment organic C (OC). However, due to limitations in current methods we do not yet fully understand which sources of C are most important to blue C ecosystems. We used environmental‐DNA (eDNA) to identify and estimate the contribution of floral sources to seagrass sediment OC sampled from three sites in Moreton Bay, Australia that differ in potential levels of autochthonous and allochthonous OC inputs. Using the plant barcode gene rbcL and a next‐generation sequencing platform we identified 150 plant operational taxonomic units in the sediment samples. We found that seagrass DNA composed on average 88% of the eDNA pool in the sediment samples. Allochtonous sources were primarily mangrove, saltmarsh, and freshwater marsh species, but the proportional contribution of other sources varied among meadows. Carbon and nitrogen (N) stable isotope mixing models suggested a lower autochthonous contribution than the eDNA data, but had high ambiguity due to indistinguishable isotopic values among some of the sources. Our study shows that eDNA can be an effective tool for identifying sources to sediment OC in blue C ecosystems and can be used in conjunction with stable isotope analysis to reduce ambiguity. Identifying the sources of OC to the sediments of blue C ecosystems is crucial for building robust and accurate C budgets for these systems.